MiR-98 reduces endothelial dysfunction by protecting blood–brain barrier (BBB) and improves neurological outcomes in mouse ischemia/reperfusion stroke model. Issue 10 (October 2020) - Bernstein, David L; Zuluaga-Ramirez, Viviana; Gajghate, Sachin; Reichenbach, Nancy L; Polyak, Boris; Persidsky, Yuri; Rom, Slava
Most neurological diseases, including stroke, lead to some degree of blood–brain barrier (BBB) dysfunction. A significant portion of BBB injury is caused by inflammation, due to pro-inflammatory factors produced in the brain, and by leukocyte engagement of the brain endothelium. Recently, microRNAs (miRNAs) have appeared as major regulators of inflammation-induced changes to gene expression in the microvascular endothelial cells (BMVEC) that comprise the BBB. However, miRNAs' role during cerebral ischemia/reperfusion is still underexplored. Endothelial levels of miR-98 were significantly altered following ischemia/reperfusion insults, both in vivo and in vitro, transient middle cerebral artery occlusion (tMCAO), and oxygen–glucose deprivation (OGD), respectively. Overexpression of miR-98 reduced the mouse's infarct size after tMCAO. Further, miR-98 lessened infiltration of proinflammatory Ly6C HI leukocytes into the brain following stroke and diminished the prevalence of M1 (activated) microglia within the impacted area. miR-98 attenuated BBB permeability, as demonstrated by changes to fluorescently-labeled dextran penetration in vivo and improved transendothelial electrical resistance (TEER) in vitro . Treatment with miR-98 improved significantly the locomotor impairment. Our study provides identification and functional assessment of miRNAs in brain endothelium and lays the groundwork for improving therapeutic approaches for patients suffering from ischemic attacks.